Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1152/jn.1995.73.5.2120
|View full text |Cite
|
Sign up to set email alerts
|

Two functionally different synergies during arm reaching movements involving the trunk

Abstract: 1. To address the problem of the coordination of a redundant number of degrees of freedom in motor control, we analyzed the influence of voluntary trunk movements on the arm endpoint trajectory during reaching. 2. Subjects made fast noncorrected planar movements of the right arm from a near to a far target located in the ipsilateral work space at a 45 degrees angle to the sagittal midline of the trunk. These reaching movements were combined with a forward or a backward sagittal motion of the trunk. 3. The dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
54
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(65 citation statements)
references
References 11 publications
(6 reference statements)
11
54
0
Order By: Relevance
“…In all conditions, the trunk began to move ϳ75 ms prior to the onset of finger motion and outlasted the duration of finger motion, consistent with findings from previous studies of reaching movements involving the trunk (Kaminski et al 1995;Ma and Feldman 1995;Pigeon et al 2000;Saling et al 1996). Nevertheless, the finger reached peak velocity relative to the trunk ϳ80 ms prior to the trunk reaching peak velocity.…”
Section: Sequencing Of Arm and Trunk Motionsupporting
confidence: 88%
“…In all conditions, the trunk began to move ϳ75 ms prior to the onset of finger motion and outlasted the duration of finger motion, consistent with findings from previous studies of reaching movements involving the trunk (Kaminski et al 1995;Ma and Feldman 1995;Pigeon et al 2000;Saling et al 1996). Nevertheless, the finger reached peak velocity relative to the trunk ϳ80 ms prior to the trunk reaching peak velocity.…”
Section: Sequencing Of Arm and Trunk Motionsupporting
confidence: 88%
“…Similar conclusions have been reached in earlier studies of trunk-assisted reaching (Adamovich et al 2001;Ma and Feldman 1995). In those studies, different trajectories in the joint configuration space were observed that maintained relative consistency of the endpoint trajectory depending on whether the trunk contributed to the movement or the trunk motion was mechanically blocked.…”
Section: The Ucm Concept and Stability Of Actionsupporting
confidence: 86%
“…In some tasks-for example, reaching with the hand to a target in front-one synergy has been found to control the trunk, independent of the motion of the hand, whereas the other synergy coordinates the motion around the arm joints to bring the hand to the target (cf. Kaminiski, 1995;Ma & Feldman, 1995;Saling et al, 1996;Wang & Stelmach, 1998). In other tasks-such as manipulation of accuracy constraints-the trunk was also shown to contribute to the focal movement (cf.…”
Section: Discussionmentioning
confidence: 99%
“…We expected the posture to be organized in two synergies: one synergy organizing the arm and the other organizing the trunk and legs (Ma & Feldman, 1995;Wang & Stelmach, 1998). To examine whether there was a synergy in the arm, we analyzed the relationship between shoulder angle and elbow angle.…”
Section: Postural Synergiesmentioning
confidence: 99%
See 1 more Smart Citation